Avaliação agronômica e nutricional do híbrido de sorgo BRS 610 em quatro estádios - Otaviano de Souza Pires Neto (2013)
The objective of this study was to evaluate the agronomic characteristics, nutritional composition and the in vitro ruminal fermentation kinetics of the whole plants and their fractions (panicle, stem and leaf) of BRS 610 sorghum hybrids at four grain stages of maturity (milky, soft dough, hard dough and hard grain) and from these data analysis recommend the best harvest age of the plant to be used as forage for ruminants. Plant stands did not change, averaging 145,000 plants.ha - 1. Plant height also did not vary with an average of 2.30 meters. The percentage of leaf fraction remained constant during the period studied, however the panicle and stem fractions behaved different (P < 0.05) with the stem fraction being diluted by the panicle fraction with the advancing maturity of the plant. Leaf fraction was the only one that had the green matter production (GMP) decreased on the older age (P < 0.05) while the whole plant GMP, panicle and stem fractions did not vary. Panicle and stem fractions showed an inverse behavior on dry matter production (DMP) (P < 0.05): while panicle DMP increased, stem DMP decreased with age advance. Additionally, whole plant and leaf fraction did not change DPM over the time. The panicle and stem fractions showed different behaviors on digestible dry matter production (DDMP), with panicle production increasing and stem production decreasing with plant maturity (P < 0.05) , however the whole plant DDMP and leaf fraction DDMP did not vary . Regarding the nutritional value, the dry matter (DM) content increased (P < 0.05) in the whole plant, panicle and leaf fractions but the stem fraction had a constant DM concentration during the period studied. The whole plant was the only one that had a quadratic response (P < 0.05) for crude protein (CP), since all the fractions had decreasing values of CP (P < 0.05) with the advancing maturity of the plant. Whole plant maintained constant levels of insoluble neutral detergent fiber (NDF) and acid detergent insoluble fiber (ADF) with advancing age. Hemicelluloses and cellulose values decreased (P < 0.05) in the whole plant with advancing age but lignin values increased (P < 0.05) in the whole plant. All fibrous fractions (NDF, ADF, hemicelluloses, cellulose and lignin) decreased (P < 0.05) on panicle fraction with advancing age of the plant. The leaf and stem fractions contents of all the fibrous fractions ( NDF, ADF , hemicelluloses , cellulose and lignin ) increased P < 0.05) with maturity of the plant , except for hemicelluloses content that showed a linear decrease (P < 0.05) as a function of the plant harvest age . Mineral matter (MM) content of behaved different in panicle and stem fractions (P < 0.05) decreasing in panicle and increasing in stems with the advancing maturity of the plant. Also, leaf fraction and whole plant contents of mineral MM remained constant throughout the evaluation period. All plant fractions studied showed a linear decrease (P < 0.05) of in vitro dry matter digestibility (IVDMD) as a function of harvesting age. Regarding the kinetics of ruminal fermentation in vitro, the whole plant with grains on the milk stage produced a larger amount of gas (P < 0.05), therefore being the most degraded (P < 0.05) of all. The panicle fraction showed no difference in gas production on the different harvest ages, however the leaf and stem fractions produced higher (P < 0.05) amount of gas when harvested on milky grain stage. All fractions had the effective in vitro dry matter degradability (EDIVMD) decreased with plant maturity. According to the presented results it is recommended to harvest the plant on the milky stage of grain.